The Spanish empire in America - Haring, Clarence Henry, 1885-1960 (San Diego : Harcourt Brace Jovanovich, 1975)
Reprint: Originally published: New York: Oxford University Press, 1947
Includes bibliography and index
Keywords: Latin America -- History -- To 1830; Spain -- Colonies -- America -- Administration